Report Calls for U.S. National Sustainability Policy. (16th July 2013) - Showstack, Randy
Abstract : The White House should issue an executive order establishing a U.S. national sustainability policy, according to a new report by a committee of the U.S. National Research Council (NRC) of the National Academies. The 28 June report found that sustainability issues inherently involve connections among environmental, economic, and social issues and that the U.S. federal government "is generally not organized or operated to deal with this complexity." The report calls for a sustainability policy to address intertwined environmental, economic, and societal issues that require interagency cooperation.